Development of chiral metal amides as highly reactive catalysts for asymmetric [3 + 2] cycloadditions - Yamashita, Yasuhiro; Yoshimoto, Susumu; Dutton, Mark J.; Kobayashi, Shū (Beilstein Journal of Organic Chemistry, 2016)
Highly efficient catalytic asymmetric [3 + 2] cycloadditions using a chiral copper amide are reported. Compared with the chiral CuOTf/Et3N system, the CuHMDS system showed higher reactivity, and the desired reactions proceeded in high yields and high selectivities with catalyst loadings as low as 0.01 mol %.
Keywords: [3 + 2] cycloaddition; asymmetric reaction; catalytic reaction; low catalyst loading; metal amide